PENGARUH SOSIALISASI, TINGKAT PENDIDIKAN, DAN PEMAHAMAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK UMKM - Anggraeni, Alqarana Maylinda; Ramayanti, Rizka (TRILOGI ACCOUNTING & BUSINESS RESEARCH, 2023)
MSME tax is one of the national development sources. This study aimed to evaluate the relationship between tax socialization, education level, taxation comprehension, and government regulation No. 23 of 2018 on MSME taxpayer compliance. This research was done by forty East Jakarta MSME respondents. Utilizing Partial Least Square, the SmartPLS application conducts data analysis. This study demonstrates that tax socialization and comprehension affect MSME taxpayer compliance, while education level has no effect.Keywords: Tax Socialization, Education Level, Tax Understanding PP No. 23 of 2018